2019
DOI: 10.3390/v11060537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marek’s Disease Virus VP22 Tegument Protein Domains Essential for Virus Cell-to-Cell Spread, Nuclear Localization, Histone Association and Cell-Cycle Arrest

Abstract: VP22 is a major tegument protein of alphaherpesviruses encoded by the UL49 gene. Two properties of VP22 were discovered by studying Marek’s disease virus (MDV), the Mardivirus prototype; it has a major role in virus cell-to-cell spread and in cell cycle modulation. This 249 AA-long protein contains three regions including a conserved central domain. To decipher the functional VP22 domains and their relationships, we generated three series of recombinant MDV genomes harboring a modified UL49 gene and assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…The intron I1 we identified could potentially represent a new protein-coding transcript which is transcribed from the UL49 locus of MDV strain CVI-988. It is reported that the VP22 protein of MDV is involved in cell cycle arrest, virus spread and histone association during MDV replication in vitro (32). Further studies will be required in order to investigate the involvement of the I1 transcript in the interaction between virus and host.…”
Section: Discussionmentioning
confidence: 99%
“…The intron I1 we identified could potentially represent a new protein-coding transcript which is transcribed from the UL49 locus of MDV strain CVI-988. It is reported that the VP22 protein of MDV is involved in cell cycle arrest, virus spread and histone association during MDV replication in vitro (32). Further studies will be required in order to investigate the involvement of the I1 transcript in the interaction between virus and host.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallography has revealed that VP22 of HSV-1 shares extensive structural similarity with ORF52 of Murid herpesvirus-68 (MHV-68) (subfamily Gammaherpesvirinae ) ( Song et al, 2005 ; Bortz et al, 2007 ). Comparisons of the sequences of VP22 in different viruses have indicated that the core domain length is 78–79 amino acids and is present in different positions of VP22 homologs ( Trapp-Fragnet et al, 2019 ).…”
Section: Features Of Vp22mentioning
confidence: 99%
“…However, amino acids 191–249 of VP22 are not essential for MDV transmission; rather, they facilitate efficient cell-to-cell spread. Amino acids 174–190 are essential for MDV VP22 functionality, and the IKIT motif (amino acids 159–162), located in the predicted β-strand, plays key roles in nuclear localization, histone association, and cell cycle arrest ( Trapp-Fragnet et al, 2019 ) ( Table 2 ).…”
Section: Features Of Vp22mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, MDV-encoded tegument proteins perform both regulatory and structural roles in the viral replication. For instance, one of the major tegument protein VP22, encoded by UL49, was indispensable for the propagation of MDV mainly relying on its N-terminus central domain, which might affect viral replication through modulating cell cycle metabolism [ 10 ]. The tegument proteins in cluster UL46–UL49 are conserved and play different roles in viral replication.…”
Section: Introductionmentioning
confidence: 99%